Which is the Best Predictive Factor of Ovarian Response; Age, Basal FSH or Basal Estradiol - Çetin, Turan; Demir, Cansun; Kıran, Hakan; Narpay, Orhan; Ürünsak, İbrahim Ferhat and Toksöz, Levent and Evrüke, Cüneyt (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: We have investigated the association between basal estradiol, FSH, age and ovarian response in the present study. STUDY DESIGN: Three- hundred twenty- nine cycles from 285 patients who admitted to Cukurova University IVF Unit were evaluated. Hormone analysis was done at one day between 3rd-5th day of the menstruel cycle. A long stimulation protocol was used with GnRHa / HMG or recFSH / HCG. 34-35h after HCG injection, an ultrasound guided transvaginal ovum pick up was performed under general anesthesia. RESULTS: The mean age of the patients was 32.49 ± 0.29 range (19-45). The mean basal FSH levels were 7.40±0.24 mIU/ml (11.38-39.69), mean LH levels were 5.9<±0.19 mIU/ml (1.26-24.68) and mean basal E2 levels were 59.40±1.20 pg/ml (17.102). The mean number of follicles which were ≥18mm and aspirated was 7.04±0.29 with a maximum of 22 follicles. The mean of oocytes picked up was 6.14±0.27 with a maximum of 21. Cycle cancellation rate after IVF was found lower in patients younger than 40, have FSH level < 12 mIU/ml. and estradiol level < 80 pg/ml. CONCLUSIONS: We found that basal FSH was more useful in evaluation of ovarian response when compared with basal estradiol and age. Combination of basal FSH and E2 is safer to use together for the evaluation of ovarian response.